Emergency department crisis management example - Karakus , Ali (Bangladesh Journal of Medical Science, 2025)
Dear Editor, Disasters that concern society, such as earthquakes, landslides, floods, natural events, terrorist bombings and transportation accidents, result in the injury or death of many people. In such events, ministries, governorships, police and gendarmerie organizations, fire departments, health directorates, ambulance officers and hospital emergency department employees will take part, and then the emergency response plans of these units will be put into action. 1-3 Disasters are extraordinary situations that hospitals and the mentioned units do not encounter frequently and may cause difficulties in their management. Emergency departments in hospitals are the units that will manage disaster situations. However, most emergency departments may not be able to respond appropriately to disasters with their current infrastructure and workforce opportunities. Social media and the public also play a major role in the execution and shaping of these disasters. The general conditions of two cases brought to the emergency department after the terrorist bombing were poor, they were unconscious and had multiple traumas that occurred after blunt and penetrating injuries to their entire body. 4-7 After the first intervention and examinations, the cases were admitted to the relevant departments. Before the cases were taken to the emergency department, information was provided about the injured with the coordination of the health directorate and 112 after the crisis management at the provincial level. 1-3 It was requested to act in line with the possible negative situations and possible increases in the number of injured. Thereupon, in line with the disaster plan previously created at the hospital level, the chief physician authorities, the health personnel responsible for the disaster plan, and the technical department personnel were made ready at their places of duty. The cases who could be discharged in the emergency department were sent and the emergency department was evacuated, and the cases other than the bombing were directed to other health institutions. Mechanical ventilators, monitors, surgical instruments that could be required for intervention, and ultrasonography devices were kept ready at the bedside. The operating department, department and intensive care units were made ready with their personnel. Teams were formed by the police and gendarmerie teams outside the emergency department and security was provided. Information was provided about the need for blood and support through the governor’s office and social media, and support was requested. In order to prevent possible negative situations during a disaster, “Emergency Planning” should be done in advance. The functionality of these plans should be evaluated with desktop and practical exercises. BJMS, Vol. 24 No. 03 July’25 Page : 1014-1015